2015
DOI: 10.1007/s00044-015-1424-7
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anticholinesterase activities of lupane triterpenoids and other constituents of Salvia trichoclada

Abstract: The methanol extract of the aerial parts of Salvia trichoclada Bentham (Lamiaceae) was studied for bioactive non-volatile secondary metabolites, and nine compounds were isolated. Structures of the isolated compounds were elucidated as lupeol (1), lupenone (2), glochidone (3), monogynol A (4), oleanolic acid (5), ursolic acid (6), b-sitosterol (7), apigenin-7-O-rhamnoside (8), and rosmarinic acid (9) by using 1D and 2D-NMR spectroscopic techniques. A lupane triterpene glochidone was isolated from a Salvia speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…A literature survey showed that 6,7-dehydroroyleanone showed higher DPPH free radical scavenging effect than ABTS cation radical scavenging activity [38], ferruginol possessed high ABTS cation radical scavenging effect [15], β-sitosterol, stigmasterol, lupenone, ursolic and oleanolic acids, and taraxasterol exhibited moderate antioxidant activity in DPPH, ABTS and CUPRAC assays [40,41] as indicated in the current work.…”
Section: Antioxidant Activity Of the Isolated Secondary Metabolitessupporting
confidence: 73%
“…A literature survey showed that 6,7-dehydroroyleanone showed higher DPPH free radical scavenging effect than ABTS cation radical scavenging activity [38], ferruginol possessed high ABTS cation radical scavenging effect [15], β-sitosterol, stigmasterol, lupenone, ursolic and oleanolic acids, and taraxasterol exhibited moderate antioxidant activity in DPPH, ABTS and CUPRAC assays [40,41] as indicated in the current work.…”
Section: Antioxidant Activity Of the Isolated Secondary Metabolitessupporting
confidence: 73%
“…In Salvia species, hydrophilic solvents are widely used to extract flavones. For instance, methanolic, ethanolic, and aqueous mixtures have been used to extract various compounds, mostly luteolin and apigenin derivatives, including glucoside and glucuronides, along with hydroxylated and methylated derivatives [36,[82][83][84][85][86][87][88][89][90][91][92]. In contrast, other polar solvents such as acetone and ethyl acetate are less used to extract these compounds [32,37,[93][94][95], while dichloromethane is even less common [96,97].…”
Section: Extraction Methods Of Flavones From Lamiaceae Plants 41 Conventional Methodsmentioning
confidence: 99%
“…ESI‐MS m / z 455.3496 [M‐H] − . It was determined as ursolic acid by comparison with the published data in the literature (Çulhaoğlu et al., 2015).…”
Section: Resultsmentioning
confidence: 99%